2017
DOI: 10.18535/jmscr/v5i10.36
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Refractive Error and Color Blindness in Truck Drivers

Abstract: Introduction: There has been a steep increase in Road traffic accidents in the last two decades in developing nations such as India. Driving has become a visually intensive task which requires sensory ability (mainly visual), mental ability and compensatory abilities. As per the Motor Vehicles Act,1988. and Central Motor Vehicles Rules, 1989, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[2,3,[13][14][15][16][17] However, literature on eyecare amongst truck-drivers, particularly in India, has focused on prevalence and types of refractive errors. [18][19] While a report does discuss spectacle usage by this mobile population, [20] our study would be the first of its' kind, both globally, and in India, to assess barriers to eyecare services for truck-drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3,[13][14][15][16][17] However, literature on eyecare amongst truck-drivers, particularly in India, has focused on prevalence and types of refractive errors. [18][19] While a report does discuss spectacle usage by this mobile population, [20] our study would be the first of its' kind, both globally, and in India, to assess barriers to eyecare services for truck-drivers.…”
Section: Discussionmentioning
confidence: 99%
“…In a US study of longhaul truckers, 75% reported good health, but were later diagnosed with a range of lifestyle diseases. [27] Studies from north and south India, report prevalence of refractive error in truck-drivers to be 17.14% and 28.57%, respectively, [18][19] depicting the persistence of the problem, despite low felt need and awareness. Another explanation for this could be drivers' remuneration, which they may perceive as being adversely affected by sick days, thus, building pressure for non-top work to maximize earnings.…”
Section: Discussionmentioning
confidence: 99%